Investigation of correlation between characteristics of Raman spectra and parameters of data-scattering obtained from phase coherence theory - PEROVA, TANIA; MOORE, ALAN (SPIE, 2005)
The importance of sensitive monitoring of changes in Raman spectra in particular for microelectronic applications is discussed here. We explore the practicality of using a data-scattering method to analyse Raman spectra, and to establish the dependence of changes observed in all the spectral function characteristics on the parameters of data-scatter such as scatter closeness and scatter radii using ?Trace Miner? software. In addition to the analysis performed on model data, analysis on experimental Raman data is also discussed. The sensitivity of the approach is fully appreciated.
PUBLISHED
Keywords: phase coherence theory; data-scattering theory; Raman spectroscopy